Routine Language: Speech Directed to Infants During Home Activities. Issue 6 (15th May 2018) - Tamis‐LeMonda, Catherine S.; Custode, Stephanie; Kuchirko, Yana; Escobar, Kelly; Lo, Tiffany
Abstract : Everyday activities are replete with contextual cues for infants to exploit in the service of learning words. Nelson's (1985) script theory guided the hypothesis that infants participate in a set of predictable activities over the course of a day that provide them with opportunities to hear unique language functions and forms. Mothers and their firstborn 13‐month‐old infants ( N  =   40) were video‐recorded during everyday activities at home. Transcriptions and coding of mothers' speech to infants—time‐locked to activities of feeding, grooming, booksharing, object play, and transition—revealed that the amount, diversity, pragmatic functions, and semantic content of maternal language systematically differed by activity. The activities of everyday life shape language inputs to infants in ways that highlight word meaning.